Prenatally Diagnosed Testicular Torsion: A Rare Condition That Causes Dilemma in Management. (18th January 2021) - Gerbo, Michael; Crigger, Chad; Samadi, Yasamin; Ost, Michael C.; Al-Omar, Osama
Abstract : Background . Prenatal testicular torsion (PTT) is exceedingly rare in intrauterine development, often diagnosed at the time of birth and very rarely diagnosed in utero during routine gestational ultrasound. As a result, incidence is unknown, and there exists no consensus regarding the pathophysiology of this phenomenon nor universally recognized algorithms and guidelines regarding its diagnosis and management. Case Presentation . We present the case of an antenatally diagnosed torsion and our subsequent management which included ipsilateral orchiectomy and prophylactic contralateral orchiopexy via a scrotal approach. Conclusion . While controversy regarding surgical intervention in patients with unilateral PTT exists due to poor salvage rates—estimated to be less than 1%—the risk of anorchia is higher in affected patients due to limitations in the accuracy of detecting bilateral testicular involvement. Risk of misdiagnosis of bilaterality may lead to lasting sequelae such as infertility and devastating psychological consequences for affected patients, supporting the need for surgical exploration, as was performed in our case.